MITIGATING OVERCONFIDENCE BIAS IN INVESTMENT BEHAVIOR: THE ROLES OF FINANCIAL LITERACY AND DIGITAL FINANCIAL LITERACY - Muhammad Saiful Hakim; Radini Vindy Setyaningrum; Rizki Dini Sandra Yunita; Ninditya Nareswari (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Previous researches have suggested the role of financial literacy in mitigating the effects of overconfidence bias. Nevertheless, there is currently no research available on the examination of digital financial literacy in mitigating the impact of overconfidence bias. Therefore, this study investigates the association between overconfidence bias and investment behavior, with a focus on the mitigating roles of financial literacy and digital financial literacy. Using the PLS-SEM approach in testing the hypotheses, this study sample comprises individuals from the millennial generation who routinely utilize investment applications on their mobile phones. The empirical result shows that overconfidence bias has a strong association with investment behavior. In addition, our findings indicate that possessing financial literacy has a beneficial effect in reducing the influence of overconfidence bias. However, the digital financial literacy has contrasting effects. Individuals with a greater level of digital financial literacy are more likely to have confidence in their decision-making abilities, as they believe they have a better understanding of financial applications.